Factors affecting family members’ decisions to reveal cancer diagnoses to patients: A qualitative study - Kanokporn Pinyopornpanish (2018)
© 2017, Medical Association of Thailand. All rights reserved. Objective: To explore the factors affecting the family members’ decisions on telling the diagnosis to cancer patients. Material and Method: A qualitative study was conducted using semi-structured, face-to-face interview with 25 close relatives of cancer patients. Content analysis was performed by two independent physicians who then collaborated to reach the conclusions. Results: Relatives primarily preferred the patient not knowing the diagnosis before the disclosure was made, to prevent the patient from getting worse. Factors associated with this preference included personal experience with cancer patients, the patient’s personal characteristics, impact of the disease on the patient’s future, the prognosis of the disease, and supporting ideas from other relatives. Once the diagnosis had been disclosed, more participants agreed with the disclosure because of the advantages to the patient and themselves. There were only two who found the advantages but still did not agree with the disclosure. Conclusion: Many factors were associated with willingness of relatives to disclose the diagnosis to the cancer patients. However, after disclosure, relatives saw advantages in terms of health care for the patients. Most family members changed their attitudes to a more positive and supportive view of disclosure.